The criminal legal consequence for Non-compliance with protection measures due to acts of family violence and violence against women - Larico Portugal, Jorge Josmell (2022)
The purpose of this article is to determine the legal consequence of non-compliance with the protection measures issued in the framework of a process for acts of violence against members of a family group, since there is a normative juxtaposition between the crime of family violence and against women and the crime of resistance or disobedience to authority. First, a normative historical study will be developed regarding violence against members of the family group and against women. Subsequently, we will carry out a study on the crime of resistance or disobedience to authority. In addition, we will expose criminal law pills on crime competition, which will allow the problem to be elucidated. Finally, we propose an alternative solution, indicating that we are facing an apparent competition of laws, therefore, the application of the aggravating circumstance of the crime of violence against members of a family group and against women corresponds, as it is a more benign norm.